A DFT investigation of the adsorption mechanism of paclitaxel on functionalized graphene oxide for enhanced drug delivery - Bader Huwaimel; Saad Alqarni (Scientific Reports)
Abstract The development of effective drug delivery systems is vital for enhancing the therapeutic efficacy of anticancer agents, particularly paclitaxel (PTX). Despite its potent anticancer properties, PTX faces limitations due to poor solubility and non-specific distribution, leading to significant side effects. To address these challenges, researchers have explored the use of reduced graphene oxide (rGO) as a nanocarrier. Functionalized rGO exhibits unique physicochemical properties, including high surface area and biocompatibility, which enhance drug loading capacity. This study investigates the adsorption mechanisms of PTX on various functionalized rGO surfaces, utilizing computational methods such as Density Functional Theory and Molecular Dynamics simulations. The results demonstrate that functionalization with hydroxyl (-OH), carboxyl (-COOH), and sulfonic (-SO) groups significantly influences the adsorption energy and charge transfer characteristics of PTX on GO. The adsorption energies calculated for PTX@rGO-OH and PTX@rGO-COOH were found to be -0.76 eV and − 0.91 eV, respectively, indicating physisorption predominantly through hydrogen bonding. In contrast, PTX@rGO-SO exhibited a higher adsorption energy of -2.09 eV, suggesting chemisorption facilitated by stronger covalent interactions. The presence of these functional groups also enhanced the binding affinity and stability of the drug-nanocarrier complex. Charge transfer analysis revealed that the rGO-COOH and rGO-SO systems exhibited significant changes in electronic properties, with charge transfers estimated at -0.16e and − 0.08e, respectively. These results indicate enhanced electronic coupling between PTX and the functionalized rGO surfaces, which can improve drug loading efficiency and release kinetics. The study also highlights the importance of optimizing surface chemistry to maximize drug interactions, leading to improved therapeutic outcomes. In conclusion, the investigation underscores the potential of functionalized graphene oxide as a promising platform for drug delivery systems. The findings, including the adsorption energies and charge transfer data, provide valuable insights into the interactions between PTX and functionalized rGO, paving the way for the design of optimized nanocarriers capable of enhancing the efficacy of anticancer therapies. The continued exploration of these systems is essential for advancing the field of nanomedicine and improving treatment strategies for cancer patients.